(3GdOjebQGWjI ai GdESdGes - (3YHGS eMehO GdYbGO(B.s; (3YHGS eMehO GdYbGO(B.s ((3GdbGgQI (B:s (3fgVI eUQ ddWHGYI hGdfTQ hGdJhRjY(B,s, 2005)
(3GdOjebQGWjI ai GdCOjGf hGdOjebQGWjI GdYQHjI ai GdSjGSI hGdGbJUGO hGdJTQjY hGdYdGbGJ GdNGQLjI hCbhGd GdeacQjf GdESdGejjf(B.s
(3eG gi GdOjebQGWjI heG JMedg ef eYfi ai LejY GdeLGdGJ(B.s
All age.
Keywords: (3GdESdGe hGdOjebQGWjI(B.s; (3GdfXGe GdSjGSj (B- (3GdESdGe(B.s; (3GdESdGe (B- (3fXGe GdMce(B.s